Low incidence of D alloimmunization among patients with a serologic weak D phenotype after D+ transfusion. Issue 10 (12th July 2016) - Yazer, Mark H.; Brunker, Patricia A.; Bakdash, Suzanne; Tobian, Aaron A.R.; Triulzi, Darrell J.; Earnest, Victorea; Harris, Samantha; Delaney, Meghan
Abstract : BACKGROUND: By consensus definition, the red blood cells (RBCs) of patients that react weak to 2+ in the serologic D test are classified as having the serologic weak D phenotype (weak D). The risk of D alloimmunization in patients with weak D is not well studied. This study retrospectively determined the incidence of D alloimmunization in patients with weak D who received D+ blood products. STUDY DESIGN AND METHODS: Patient records at four institutions were reviewed. Eligible patients had at least 1 D typing result with agglutination strength that was weak to 2+ result in gel or tube (Institutions 1‐3) or weak to 2+ result in solid phase or a positive tube weak D test using antihuman globulin reagent (Institution 4). All patients received at least 1 D+ allogeneic RBC or platelet transfusion and had a subsequent antibody detection test performed at least 30 days after the first D+ transfusion. RESULTS: The incidence of alloanti‐D formation was 0.15% (6/4011, at Institutions 1‐3) and 5.1% (3/59, at Institution 4; these incidences were significantly different [p = 0.0002]). There were 0.15% (6/4011) patients who had autoanti‐D detected; all were at Institutions 1 to 3. CONCLUSIONS: Until RHD genotyping is widely available, these data support the fact that patients with serologic weak D may be transfused with D+ RBCs if an urgent transfusion is required. At Institution 4, inclusion of a higher proportion of black patients compared to the other institutions may have affected the incidence of alloimmunization by perhaps including partial D recipients who are at risk of forming D antibodies.